2004
DOI: 10.1021/bp034362x
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Lyophilization is the most popular method for achieving improved stability of labile biopharmaceuticals, but a significant fraction of product activity can be lost during processing due to stresses that occur in both the freezing and the drying stages. The effect of the freezing rate on the recovery of herpes simplex virus 2 (HSV-2) infectivity in the presence of varying concentrations of cryoprotectant excipients is reported here. The freezing conditions investigated were shelf cooling (223 K), quenching into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 37 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The first design of experiment approach was based on the most commonly used lyoprotectants, i.e., sucrose, trehalose and mannitol, in combination with dextran, with and without NaCl (Table SI , supplemental data). These excipients are known to provide physical and biochemical stabilization as well as appropriate structural properties to the cake structure, during and after lyophilization ( 29 – 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first design of experiment approach was based on the most commonly used lyoprotectants, i.e., sucrose, trehalose and mannitol, in combination with dextran, with and without NaCl (Table SI , supplemental data). These excipients are known to provide physical and biochemical stabilization as well as appropriate structural properties to the cake structure, during and after lyophilization ( 29 – 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, decreases in viral titre correlate with demonstrable changes since the viral envelope is assumed to be associated with viral infectivity [ 11 ]. Lyophilization of a heat-labile lipid-enveloped virus such as Herpes simplex virus pointed out that high concentration (27% w/v) of stabilizers could achieve up to 80% recovery of the viral titre [ 23 ]. In our study, similar results were observed with HSV.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have investigated the structure of reverse micelles formed under extreme conditions such as high vacuum or cryogenic temperatures. Our interest in the latter case was inspired by the increasing industrial exploitation of cryogenic techniques in biomedicine for the long-term preservation of biological materials in combination with the ability of reverse micelles to model and/or to mime some fundamental aspects of biomembranes. , Moreover, investigations of the processes occurring during fast freezing of microheterogeneous systems could also be of theoretical and technological interest. Information in this field is mostly obtained by freeze-fracture TEM and more recently by cryoTEM techniques.…”
Section: Introductionmentioning
confidence: 99%